CONDIÇÃO E TRATAMENTO PERIODONTAL NO TRANSPLANTADO RENAL. - SANTOS, Danila Lorena Nunes dos (2019)
The inflammatory process may be associated with the failure of organ transplantation. Chronic periodontitis is also characterised as an inflammatory process with possible systemic repercussions, although a causal or co-morbid role is unknown. The first chapter deals with a systematic review whose objective was to identify the clinical findings associated with the periodontal condition in renal transplant patients. The systematic review included crosssectional, case-control and cohort studies published up until August 2018 in PubMed/Medline, Scopus, Science Direct and CENTRAL. The research used the following descriptors: "kidney transplantation", "chronic renal failure", "periodontal diseases", "periodontitis", "chronic periodontitis", "gingival hyperplasia" and "gingivitis". The outcomes comprised the clinical variables of transplantation. Two independent reviewers extracted the data and assessed the quality of the studies using the Newcastle-Ottawa scale. The electronic search revealed 1,063 potentially relevant studies. We selected 114 articles for the reading of the full text (complete reading). After complete reading, 108 studies were excluded, six studies met the eligibility criteria of the review: one case-control, three transverse and two cohorts. All the studies showed a low risk of bias according to the Newcastle-Ottawa scale. The findings suggest that the periodontal status may be associated with a greater left ventricular mass, a greater carotid thickness and a higher mortality rate in 60 months later. One possible hypothesis that establishes a relationship between the presence of periodontal disease to left ventricular hypertrophy is the influence of inflammatory mediators on the cardiac muscle. With due restrictions, it is possible to conclude that there is a relationship between the periodontal status and the worsening renal graft function or worsening of systemic health in renal transplant recipients, although there is no conclusive hypothesis of causality. The second chapter deals with a non-randomised clinical trial performed with renal transplant patients who attended the Presidente Dutra University Hospital; this trial aimed to identify the clinical findings associated with periodontal treatment. A periodontal assessment was performed at least 6 months after transplantation. A periodontal examination of the whole mouth with the exception of the third molars was performed for the parameters: plaque index, gingival bleeding index (ISG), clinical insertion level (NIC), probing depth and gingival recession at six sites. The periodontal treatment of the non-surgical maintenance (scaling and root planning) followed by dental polishing was performed in a single session with periodontal curettes and ultrasound. For the statistical analysis, the Wilcoxon test and Spearman’s correlation coefficient were used to compare the parameters before and after the periodontal treatment. The reduction in the periodontal parameters was not statistically significant; however, significant changes were found in the serum creatinine ratio (p = 0.044) at time 1, the correlation analysis revealed that when there was a reduction in ISG after treatment there was a reduction in serum creatinine concentration (Rs = 0.39, P = 0.049) and a reduction in the leukocyte cell count (Rs = 0.44, P = 0.013). Of the patients evaluated, 52.27% had moderate periodontitis according to the criteria defined by the American Academy of Periodontology in 1999. The findings suggest that non-surgical periodontal treatment may be associated with a decreased creatinine level, an altered leukocyte count and uric acid.